Pengembangan Media teka teki silang materi aktivitas kebutuhan manusia di Mtsn Kota Malang - akmal, moch syarifuddin (Maliki Interdisciplinary Journal, 2025)
Learning media is an intermediary used by teachers to convey learning material. Interactive learning media will make students more active in participating in learning activities. The aim of this research is to develop learning media in the form of crossword puzzles in social studies subject material on human needs activities that can support the learning process. The method used in this research is Research and Development with the ADDIE development model. The validation results for this product are very valid with a score of 96.4% in terms of media and 95% in terms of material. This product is also stated to be very practical with scores of 95% and 85% and a completeness score of 100%.